Why religion? [compact disc, unabridged] : a personal story - Pagels, Elaine H., 1943- (HarperCollins, 2019)
Elaine Pagels draws upon on personal experiences and the perspectives of neurologists, anthropologists, and historians to illuminate the enduring capacity of faith in explaining and meeting the challenges of the twenty-first century.